2014
DOI: 10.1088/0741-3335/57/1/014038
|View full text |Cite
|
Sign up to set email alerts
|

The H-mode density limit in the full tungsten ASDEX Upgrade tokamak

Abstract: The high confinement mode (H-mode) is the operational scenario foreseen for ITER, DEMO and future fusion power plants. At high densities, which are favorable in order to maximize the fusion power, a back transition from the H-mode to the low confinement mode (L-mode) is observed. In present tokamaks, this H-mode density limit (HDL) occurs at densities on the order of, but below, the Greenwald density.In gas ramp discharges at the fully tungsten covered ASDEX Upgrade tokamak (AUG), four distinct operational pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 35 publications
12
121
0
Order By: Relevance
“…The line integrated edge density n edge ( Fig. 2 (c)), measured along the interferometry Line-Of-Sight (LOS) H-5 [20], increases during that phase from 1.1 to 3.2 × 10 19 m −3 . In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The line integrated edge density n edge ( Fig. 2 (c)), measured along the interferometry Line-Of-Sight (LOS) H-5 [20], increases during that phase from 1.1 to 3.2 × 10 19 m −3 . In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible to further illuminate how the interactions with neutrals affect blobs, and how blobs affect neutrals, with a model that include both dynamical neutrals and plasma fields. Moreover a range of experimentally observed phenomena that are most likely due to neutrals influencing the plasma fields, such as shoulder formation 30 and the fuelling triggered H-mode density limit 31 , are expected to at least be partially explained by future simulations with this model. …”
Section: Discussionmentioning
confidence: 95%
“…Had elastic collisions with neutrals been included in the model, a yet another first order drift term would be added to (31). This is the so-called Pedersen drift, and details on the derivation of the term are found in 8 .…”
Section: B Neutral Transport Modelmentioning
confidence: 99%
“…An H-mode can thus vary its Greenwald fraction below this limit, but not above it; if the tokamak seeks to maximize its density, the density will be determined by this limit. Regressions over a very limited magnetic field range (roughly 1 T to 3 T) have found that the Greenwald fraction corresponding to this H-mode density limit declines sharply with magnetic field, but the full magnetic field behavior has not been explored [26,27].…”
Section: Electron and Dt Ion Densitymentioning
confidence: 99%
“…The width of an AE may be estimated by taking (27) and solving for a mode of the form ξ ⊥ = exp [i (nφ − ωt)] m ξ ⊥,m (r) exp (−imθ). Stating the result to zeroth order in inverse aspect ratio gives [29][30][31] d dr…”
Section: Toroidal Mode Number Of Most Unstable Modementioning
confidence: 99%